Translationspolitik für Regional- oder Minderheitensprachen Unter besonderer Berücksichtigung einer Strategie der Offenheit - Sandrini, Peter (TRANSÜD. Arbeiten zur Theorie und Praxis des Übersetzens und Dolmetschens, 2018)
A reasonable evolution model is indispensable for the comprehensibility and justification of translation policy decisions. On the one hand, this model should take into account the general objectives of protecting a regional or minority language and, on the other, the findings of translation studies and the best practices of the translation industry. On the basis of these assumptions, the author derives possible lines of development for the various areas of translation policy with the help of the maturity model derived from organisational management. He also develops a comprehensive evaluation procedure: the Translation Policy Metrics Model (TPM). The exemplary implementation of this model is based on the example of the minority region of South Tyrol using two surveys, several personal interviews with leading personalities in the field of translation as well as by examining the existing sources of legislation. Peter Sandrini is a research assistant at the Institute for Translation Studies at the University of Innsbruck. His research focuses on legal translation, translation technology and terminology (www.petersandrini.net).